Early Relapsing Multiple Sclerosis. Issue 3 (June 2016) - Jones, David E.
Abstract : Purpose of Review: : This article provides an evidence-based approach to the management of patients with early relapsing multiple sclerosis (MS). Recent Findings: : Numerous clinical trials have shown the role of disease-modifying therapies in reducing relapses and new MRI lesions in patients with relapsing MS. Many of these trials also show the ability of these agents to delay disability progression, and a few suggest that disease-modifying therapies may slow brain atrophy in relapsing MS; however, very few suggest that disease-modifying therapies can improve symptoms or disability. The therapeutic armamentarium of disease-modifying therapies includes five interferon formulations, two versions of glatiramer acetate, mitoxantrone, natalizumab, fingolimod, teriflunomide, dimethyl fumarate, and alemtuzumab. Summary: : Although multiple disease-modifying therapies exist, the risks of these vary markedly, head-to-head comparator trials are limited, and no prospective biomarkers for treatment efficacy exist; therefore, choosing a disease-modifying therapy for an individual patient with MS is a difficult decision. This difficulty is compounded by limitations in predicting a patient's disease course, and the risk tolerance of the patient and opinions of the care partner need to be factored into the decision analysis as well. After a disease-modifying therapy is chosen, vigilance for clinical or radiographic breakthrough disease is very important, as this may suggest a suboptimal response to the chosen therapy. Furthermore, the role of symptom management and wellness should always remain part of the approach to the patient with MS.